Analysis of Sharia Principles Implementation in Istishna' Contracts and Its Impact on Customer Satisfaction: A Qualitative Descriptive Study at PT. Mari Beri Faedah - Aan Fajar Wijaya; Sri Hartono; Arif Hartono (Universitas Darunnajah, 2025)
This study analyzes the implementation of sharia principles in the istishna' contract and its impact on customer satisfaction at PT. Let's Give Benefits (MARIFA). This study aims to map the integration of the principles of Rabbaniyyah, Akhlaqiyyah, Waqi'iyyah, and Insaniyyah in the framework of istishna' and uncover their contribution in shaping holistic customer satisfaction. We used a descriptive qualitative approach with ethnographic methods, collecting data through participatory observation and in-depth interviews with 13 informants from directors, employees, and customers. Data analysis to obtain comprehensive findings. The results of the study revealed that MARIFA has succeeded in operationalizing the four sharia principles. The Rabbaniyyah principle gives rise to spiritual satisfaction through usury-free transactions and the creation of